Overcoming very late severe calcific stenosis due to two layers of under‐expanded stents with intravascular lithotripsy treatment: A case report. Issue 8 (21st August 2021) - Doost, Ata; Clugston, Richard
Abstract: Intravascular lithotripsy (IVL) shockwave treatment is effective in treatment of severe calcific coronary stenosis within two layers of old under‐expanded stents. Intravascular imaging is essential to analyze the mechanism of in‐stent failure and optimize treatment. Abstract : Intravascular lithotripsy (IVL) shockwave treatment is effective in treatment of severe calcific coronary stenosis within two layers of old under‐expanded stents. Intravascular imaging is essential to analyze the mechanism of in‐stent failure and optimize treatment.